A computational comparison of the multiple-breath washout and forced oscillation technique as markers of bronchoconstriction - Foy, B; Kay, D (Elsevier, 2017)
Many types of lung disease lead to constriction of airways within the conducting zone, causing increases in airway resistance and ventilation heterogeneity (VH). The multiple-breath washout (MBW) and forced oscillation technique (FOT) are two clinical measures of small airway bronchoconstriction. Within this study computational modelling of the MBW and FOT was applied to the analysis of thousands of bronchoconstriction scenarios in the conducting zone of the lungs. The simulations show that MBW indices primarily respond to the severity of constriction, while FOT indices may be able to distinguish between constrictions at differing airway depths. Following this, we show the potential utility in the joint interpretation of indices from the two tests, providing motivations for future clinical investigations.